Transmembrane Protein 230 Mediates a Poly(ADP-ribose) Polymerase-1-Linked Apoptosis - Wang, Xiaobo; Wu, Tengteng; Zhang, Jinru; Guo, Gongbo; He, XiaoFei; Pei, Zhong; Liu, Zhaohui; Liu, Chun-feng; Ross, Christopher A.; Smith, Wanli W. (Frontiers in Aging Neuroscience, 2020)
Mutations in TMEM230 (transmembrane protein 230) gene suggest to be associated with the autosomal dominant Parkinson’s disease with typical movement disorders and Lewy body pathology. However, the normal functions and the pathological roles of TMEM230 are not clear. In this study, we used TMEM230 isoform II constructs including wild type and four reported PD-linked mutation constructs (Y92C, R141L, 184Wext*5, 184PGext*5). Ectopic expression of wild type (WT) and PD-linked mutant TMEM230 variants in cultured cells dramatically induced apoptotic cell death compared with vector control cells. Mutant TMEM230 caused cell toxicity at an increased severity than WT-TMEM230. Moreover, expression of TMEM230 increased mitochondrial ROS levels, decreased cellular ATP, activated caspase 3/7 and increased PARP1 cleavage. Treatment with NAC (N-acetylcysteine, an ROS scavenger) or Z-VAD-FMK (a caspase inhibitor) significantly attenuated TMEM230-induced apoptosis in both cultured cells and primary neurons. Our results indicated that TMEM230 mediated a PARP1-linked apoptotic cell death pathway. These findings not only provide the novel insight into the biological roles of TMEM230 in PARP1-linked pathway, but also provide a TMEM230-induced cell death mechanism underlying PD pathogenesis.